2020
DOI: 10.1016/j.isci.2020.100875
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Monocular Perceptual Learning on Binocular Visual Processing in Adolescent and Adult Amblyopia

Abstract: Re-establishing normal binocular visual processing is the key to amblyopia recovery beyond the critical period of visual development. Here, by combining perceptual learning, behavioral testing, and steady-state visually evoked potentials (SSVEPs), we examined how monocular perceptual learning in the amblyopic eye could change binocular visual processing in the adolescent and adult amblyopic visual system. We found that training reduced the interocular difference between amblyopic and fellow eyes and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 45 publications
6
29
0
Order By: Relevance
“…Given the controversy that monocular training while patching the fellow eye may promote interocular suppression over binocularity (Hess et al, 2015), it is encouraging that stereoacuity thresholds improved (decreased) in both groups (Figure 4, Table S3 & Figure S11 for individual scatter plots). This finding reflects changes to observers' typical binocular vision even when not wearing an eye patch, consistent with evidence that latent binocularity remains in the amblyopic brain, and can be at least partially recovered given the right conditions (e.g., Gu et al, 2020;review: Hess et al, 2015). PL studies in amblyopia have found incidental improvements in stereoacuity (e.g., Zhang et al, 2014;reviews: Levi and Li, 2009;Hess et al, 2015;Levi, 2020;Rodan et al, 2020).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Given the controversy that monocular training while patching the fellow eye may promote interocular suppression over binocularity (Hess et al, 2015), it is encouraging that stereoacuity thresholds improved (decreased) in both groups (Figure 4, Table S3 & Figure S11 for individual scatter plots). This finding reflects changes to observers' typical binocular vision even when not wearing an eye patch, consistent with evidence that latent binocularity remains in the amblyopic brain, and can be at least partially recovered given the right conditions (e.g., Gu et al, 2020;review: Hess et al, 2015). PL studies in amblyopia have found incidental improvements in stereoacuity (e.g., Zhang et al, 2014;reviews: Levi and Li, 2009;Hess et al, 2015;Levi, 2020;Rodan et al, 2020).…”
Section: Discussionsupporting
confidence: 78%
“…Both groups also showed modest increases in the AULCSF, similar in magnitude to another VPL training study with amblyopic adults (Gu et al, 2020), convergent evidence of foveal contrast sensitivity improvements. Notably, the Attention group showed AULCSF gains in both eyes, whereas the Neutral group only showed gains in the amblyopic eye (although there was less room for improvement in the fellow eye) (Figure 4).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Age, etiology, prior treatment and baseline stereo were not associated with response to treatment Dose-response: Only in the game group, moderate linear relationship between hours of game with VA improvement. 5 h (50% adherence) improved 0.1 logMAR; 10 h (100%), 0.18 logMAR; 15 h (150%) 0.26 logMAR Single-site, small-cohort randomized clinical trial The inclusion/exclusioncriteria may limit generalization to other groups of amblyopic children VA testing was not masked Results may be dependent on the criteria chosen to dichotomize each variable The brief duration may limit improvement of VA Possible biases due to the lack of correct monitoring ( number of hours of patching objectively, not wear the red- green glasses) Parents overestimated time spent playing the game by 13% Game group completed 10.3 ± 3.0 h (103% prescribed treatment time Patching group completed 27.7 ± 2.6 h (99% prescribed treatment time) Gu et al, 2020 46 VA *** , CS *** , stereopsis * and interocular diference ** improved through behavioral measurements and SSVEP in MT group (Due to the length of the results, it is recommended to see the "results" section in the original article) Control group had only five subjects Training effects may be due to the influences of both training and patching Effects of patching were not entirely ruled out in this study. Further investigations with more subject and only training (no patching) are necessary Although no compliance data is provided, pre-post results of the 32 (out of 46) participants are presented, so it is understood that not everyone completed the training Note : A: anisometropic amblyopia; BCVA: Best corrected visual acuity; BiT: binocular treatment; cpd: cycles per degree; CS: contrast sensitivity; DT: dichoptic therapy; h: hour/ hours; IOR: interocular ratio; min: minutes; MT: monocular training; ns: no significance; PL: perceptual learning; S : strabismic amblyopia; SSVEPs: Steady-state visually evoked potentials; VA : visual acuity; VG: video game.…”
Section: Resultsmentioning
confidence: 99%
“…When performed during the critical period of development, ME induces a robust compensatory plastic response of RGCs axons from the intact eye (Godement et al., 1980; Reese, 1986). Actually, in amblyopic infant patients, the monocular patching of the non‐amblyopic eye is the current clinical practice to restore binocular visual processing, and recent reports indicate that monocular perceptual learning can be an effective therapeutical approach in adolescents and adults (Gu et al., 2020). Recently, we showed that ME performed at PND10 leads to a rapid and exuberant axonal reorganization of the intact ipsilateral pathway within the first 24–48 hr post‐lesion, which was sustained for 1 year after (Chagas et al., 2019).…”
Section: Discussionmentioning
confidence: 99%